The role of smoking and alcohol in mediating the effect of gastroesophageal reflux disease on lung cancer: A Mendelian randomization study - Yang, Jing; Nie, Duorui; Chen, Yujing; Liu, Zixing; Li, Mengzhao; Gong, Chun; Liu, Qiong (Frontiers in Genetics, 2023)
Observational studies have suggested an positive association between gastroesophageal reflux disease and lung cancer. Because of the existence of confounders, it remains undetermined whether gastroesophageal reflux disease has a causal association with lung cancer. Therefore, we employed Mendelian randomization (MR) analyses to investigate the relationship between the two conditions. Two-sample MR analysis was utilized with summary genetic data from European Bioinformatics Institute (602,604 individuals) and International Lung Cancer Consortium which provider information of lung cancer and its histological subgroups. Inverse‐variance weighted method, weighted median method, MR‐Egger regression, simple mode, weighted mode, MR Pleiotropy RESidual Sum, and Outlier test were used for MR analyses.MR analysis indicated that gastroesophageal reflux disease was associated with and significantly increased risk of lung cancer (ORIVW=1.35; 95%CI:1.18-1.54, p=1.36×10-5). In MR analysis for adenocarcinoma, squamous cell cancer and small cell cancer, the causal relationship was also substantially existed. According to our findings, gastroesophageal reflux disease has an association with an increased risk of morbidity of lung cancer, further studies are necessary to illustrate underlying mechanisms.